2010
DOI: 10.1088/0957-4484/21/12/125603
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of magnetic nanoparticles into higher structures on patterned magnetic beads under the influence of magnetic field

Abstract: The self-assembly of nanoparticles into higher organizations in a controlled manner has critical importance for the utility of the unique properties of nanoparticles. The behavior of magnetic Fe(3)O(4) nanoparticles (MNPs) with an average size of 6 nm under an enhanced magnetic force is reported. Upon evaporation of the solvent where the MNPs are suspended, formation of unique micrometer-sized structures is achieved only when there is a patterned surface constructed from sub-micrometer size magnetic beads in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…35). 207 When an external magnetic field was applied, microstructures from suspensions in the presence of magnetic beads were observed. Fig.…”
Section: Alignment Of Carbon Nanotubesmentioning
confidence: 99%
“…35). 207 When an external magnetic field was applied, microstructures from suspensions in the presence of magnetic beads were observed. Fig.…”
Section: Alignment Of Carbon Nanotubesmentioning
confidence: 99%
“…[4][5][6] Other researchers have found that magnetic nanoparticles suspended in a solvent form unique micrometre sized structures when a patterned surface of submicrometre sized magnetic beads is constructed between the magnetic field and the magnetic nanoparticles. 7 While the observed chains provide some indication that the ferrimagnetic particles align with the magnetic field lines, a detailed study to show the overall mapping of alignment and response in terms of chain length formation of ferrimagnetic nanoparticle assemblies within magnetic fields has not been performed to date.…”
Section: Introductionmentioning
confidence: 99%
“…In these years, much effort has been made to understand how magnetic fields influence the growth of crystals and the directed aggregation of nanoparticles. For example, magnetic fields were used to direct the orientation of vanadium pentoxide ribbons [5], the growth of Fe 3 O 4 nanowires [6], the assembly of magnetic nanoparticles [7][8][9][10][11], mouse osteoblast cells [12], and the alignment of grains and particles [13,14]. It has been developed as an effective auxiliary preparation method for anisotropy nanomaterials with various applications [15,16].…”
Section: Introductionmentioning
confidence: 99%